Press campaigns in Iraqi newspapers: Al-Mada newspaper as a model - Al-Mayali, Adel Hashem Mohsen (Al-Adab Journal, 2022)
The scandal of oil coupons distributed by the former regime in Iraq to a number of politicians, diplomats, journalists, writers and artists, whose value is estimated at millions of dollars, was a great transgression against the rights of the Iraqi people who did not find bread during the years of the blockade and this scandal did not appear until after the fall of system, and the success of a number of journalists in revealing its files. Al-Mada newspaper had a great role in publishing documents through a campaign that is considered the most prominent in the contemporary history of Iraq, and even at the level of the Arab press, as it provoked local, Arab and international responses and repercussions. Hence our choice of the press campaign carried out by Al-Madda as a successful model that was able to emphasize the importance of the Fourth Authority in exercising oversight, achieving justice and returning the looted funds. We have adopted an integrative methodology represented by the descriptive approach, and the content analysis was present in clarifying the campaign's methods, forms, arts and media logic on which it relied in achieving the persuasive goal of its journalistic discourse. The results came to clearly show that such a campaign, if it was repeated in the Iraqi press, would be a decisive factor in the fight against rampant corruption.